Insectopolis : a natural history - Kuper, Peter, 1958- (W. W. Norton & Company, 2025)
"This visually immersive work of graphic nonfiction dives into a world where ants, cicadas, bees, and butterflies visit a library exhibition that displays their stories and humanity's connection to them throughout the ages. Kuper's thrilling visual feast layers history and science, color and design, to tell the remarkable tales of dung beetles navigating by the stars, hawk-size prehistoric dragonflies hunting prey, and mosquitoes changing the course of human history. Kuper also illuminates pioneering naturalists, from well-known figures like E. O. Wilson and Rachel Carson to unheralded luminaries like Charles Henry Turner, the Black American scholar who documented arthropod intelligence, and Maria Sybilla Merian, the seventeenth-century German regarded as the mother of entomology. Galvanized by the sixth extinction and the ongoing insect crisis, Kuper takes readers on an unforgettable journey." --